The Sharing Economy in the Context of Sustainable Development and Social Responsibility: The Example of the Czech Republic - Jelínková, Martina; Tetřevová, Liběna; Vávra, Jan; Munzarová, Simona (MDPI, 2021)
The rapid development of the sharing economy that has been registered in recent years is caused by a number of factors. The increasingly pronounced effort on the part of all economic entities to contribute towards sustainable development through the application of socially responsible behavior is deemed to be a key factor. The objective of the article is to analyze and evaluate the attitudes of customers towards the benefits of the sharing economy in the field of economic, social, and environmental responsibility using the example of a small post-communist economy-the Czech Republic. Primary data were obtained on the basis of a questionnaire survey. This was elaborated using descriptive and inferential statistics tools. The study that was performed shows that the majority of customers regard sharing as a source of benefits in the field of economic, social, and environmental responsibility, whereas in a complex sense, they perceive these benefits to be equal. Women perceive the investigated benefits of sharing with regard to environmental responsibility as more important compared to men. In comparison with the older generation, the younger generation perceives selected benefits of sharing as more important in all three investigated areas of responsibility. People with a higher education perceive selected benefits of sharing with regard to economic responsibility as more important compared to people with a lower level of education. The article provides original insights into the perception of the benefits of sharing for sustainable development by actors in the sharing economy and is a source of knowledge about their motivations for both policymakers and managers of companies involved in the sharing economy.
Sdílená ekonomika v kontextu udržitelného rozvoje a společenské odpovědnosti: příklad České republiky
Keywords: sharing economy; social responsibility; sustainability; sustainable development; sdílená ekonomika; společenská odpovědnost; udržitelnost; udržitelný rozvoj